Changes in right ventricular deformation during hyperoxia versus normoxaemia in patients with stable coronary artery disease and healthy controls. (8th February 2021) - Sutter, CD; Fischer, K; Yamaji, K; Ueki, Y; Jung, B; Raeber, L; Von Tengg-Kobligk, H; Eberle, B; Guensch, DP
Abstract: Funding Acknowledgements: Type of funding sources: Public hospital(s). Main funding source(s): Local research funds of the Department of Anaesthesiology and Pain medicine, Bern University Hospital, Inselspital Background: During anaesthesia, emergency and critical care treatment, patients with coronary artery disease (CAD) are often exposed to supraphysiologic arterial oxygen tensions. The balance between benefits and risks of hyperoxia (HO) in patients with stable CAD is controversial, with reports about reduced left ventricular contractility or increased morbidity and mortality. Effects of HO on right ventricular (RV) function in CAD are less well described. Advanced cardiovascular magnetic resonance (CMR) feature tracking software allows assessment of myocardial deformation, which may serve as early marker of ventricular dysfunction. In a CMR study we quantified the effect of HO on RV function and deformation in awake healthy participants and CAD patients. Methods: Ten healthy participants and 26 patients with stable one- or two-vessel obstructive CAD were included. In a CMR study, a short-axis function stack of both ventricles was obtained first at room air (RA), then during HO induced by breathing oxygen at 10L/min for 5 minutes via a non-rebreathing facemask. RV strain was analysed by a blinded reader who manually traced epicardial and endocardial contours of the RV for determining peak global circumferential strain (RVGCS), time to peak strain, systolic and diastolic strain rate parameters. Results: RV ejection fraction did not change with O2 breathing in the healthy control group (RA, 56 ± 12% vs. HO, 55 ± 10%, p = 0.999) nor in the CAD group (RA, 60 ± 8% vs. HO, 60 ± 9%, p = 0.609). RV cardiac index decreased significantly in CAD patients from RA (2.62 ± 0.88 L/min/m2) to HO (2.42 ± 0.77L/min/m2, p = 0.002). The decrease in the control group was not significant (RVCI: RA 3.28 ± 1.29 vs HO 3.04 ± 1.27L/min/m2 p = 0.068). In the healthy control group, RVGCS, time to peak strain, and systolic strain rate did not change significantly with HO (RVGCS: RA, -14.6 ± 3.9% vs. HO, -13.1 ± 4.5%, p = 0.353; time to peak strain: 282 ± 45ms vs. 286 ± 29ms, p = 0.540; and systolic strain rate: -0.85 ± 0.27/s vs. -0.67 ± 0.28, p = 0.055). In CAD patients RVGCS worsened from -14.8 ± 3.3% on RA to -13.9 ± 3.6% at HO (p = 0.040). Time to peak strain became significantly prolonged from 319 ± 40ms on RA to 329 ± 49ms at HO (p = 0.046). This was accompanied by a reduction of systolic strain rate from -0.79 ± 0.27/s to -0.75 ± 0.22/s (p = 0.037). Diastolic strain parameters did not differ significantly between RA and HO in either group. Conclusion: In our cohort of CAD patients HO significantly reduced RV cardiac index and impaired systolic deformation as determined by CMR feature tracking. Studies are required in a larger patient cohort with regional analysis and assessment of longitudinal and radial deformation to assess the role of hyperoxia in CAD.